Development and characterization of the genotype F attenuated mumps candidate strains - Liu, Hongtao; Liu, Na; Sun, Yueqiu; Li, Shuang; Li, Hang; Wang, Menghan; Shuang, Hui; Cai, Yan (Frontiers in Immunology, 2025)
BackgroundMumps is an acute infectious disease caused by the mumps virus (MuV), primarily affecting the parotid glands, though it can also lead to systemic infections, including the nervous system. In China, the predominant circulating MuV genotype is F, while the vaccine strain (S79 or WM84) belongs to genotype A, raising concerns about immunization effectiveness.MethodsA genotype F MuV strain was isolated from throat swabs of six suspected mumps patients. Through cell adaptation passage and plaque purification, two candidate vaccine strains QBB-2BS-3.2 and QBB-2BS-9.3 were prepared. Their immunogenicity was assessed by neutralizing antibody and cell-mediated immune responses in immunized mice. Additionally, neurotoxicity was evaluated in neonatal Lewis rats.ResultsBoth QBB-2BS-3.2 and QBB-2BS-9.3 elicited strong neutralizing antibody responses and robust cell-mediated immune responses in mice. Notably, neurotoxicity testing revealed minimal neurotoxicity in QBB-2BS-3.2 and QBB-2BS-9.3 strains, comparable to the S79 vaccine strain.ConclusionsThis study successfully developed two attenuated genotype F MuV candidate strains with favorable immunogenicity and safety profiles, laying a critical foundation for the development of genotype F mumps live attenuated vaccines.